Nasopharyngeal Carcinoma: Connecting Antemortem and Postmortem Findings to Highlight a Rare Case of EBV and HPV Negativity - Thomas Auen; Geoffrey Talmon (Case Reports in Pathology)
Nasopharyngeal carcinoma is an endemic entity with a strong association with Epstein-Barr virus and a new recognition of human papilloma virus-mediated effects in nonendemic areas. Here, we discuss a nasopharyngeal carcinoma suspected as based on imaging results with metastasis to the lymph nodes, lung, spleen, bone, and liver. Gross and microscopic findings from the autopsy were clinicopathologically correlated with antemortem clinical studies and investigations. The authors report a case of EBV- and HPV-negative nonendemic, multisite metastatic nasopharyngeal carcinoma, shown to be nonkeratinizing undifferentiated subtype.